ANALYSIS OF THE FOUNDATION DESIGN FOR THE LOWER STRUCTURE OF THE CIBEET RIVER BRIDGE (STA 0+952), DELTAMAS CITY - Mochamad Iqbal Nugraha; Pio Ranap Tua Naibaho; Hikma Dewita (University Muhammadiyah Jakarta, 2026)
The substructure of a bridge plays a vital role in ensuring the stability and safety of the bridge structure by transferring loads from the superstructure to the supporting ground. The construction of the Cibeet River Bridge at STA 0+952 in Deltamas City requires a reliable foundation system due to varying subsurface soil conditions. Therefore, evaluating the bearing capacity and structural performance of the bridge abutments and bored pile foundations is crucial. This study aims to analyze the results of soil investigations obtained from field and laboratory tests, determine the bearing capacity of the bored pile foundations, and evaluate the structural design of the bridge abutments. The research methodology involved a literature review, collection of bridge design data, and analysis of geotechnical investigation data, including Standard Penetration Tests (SPT), Cone Penetration Tests (CPT), borehole logs, and laboratory tests. The structural analysis considered dead loads, earth pressure, additional loads, traffic loads, braking loads, and seismic loads acting on the abutments. The research results indicate that the selected bored pile foundations provide sufficient bearing capacity to support the applied structural loads, while the abutment design meets the required structural strength and stability criteria. Strengthening analyses for the abutment walls, pile heads, and bored piles also indicate that the designed reinforcements meet the structural requirements under the applicable load combinations. Overall, the planned bridge substructure is capable of safely transferring loads to the foundation system and is considered suitable for implementation in the Cibeet River Bridge project. Keywords: Bridge, Abutment, Bored Pile, Bearing Capacity, Soil Investigation.